Contemporary research on business and management proceedings of the International Seminar of Contemporary Research on Business and Management (ISCRBM 2019), 27-29 November, 2019, Jakarta, Indonesia - International Seminar of Contemporary Research on Business and Management (2019 : Jakarta, Indonesia); Noviaristanti, Siska (Leiden, The Netherlands : CRC Press/Balkema, 2021)
This book contains selected papers presented at the 3rd International Seminar of Contemporary Research on Business and Management (ISCRBM 2019), which was organized by the Alliance of Indonesian Master of Management Program (APMMI) and held in Jakarta, Indonesia on 27-29th November 2019. It was hosted by the Master of Management Program Indonesia University and co-hosts Airlangga University, Sriwijaya University, Trunojoyo University of Madura, and Telkom University, and supported by Telkom Indonesia and Triputra. The seminar aimed to provide a forum for leading scholars, academics, researchers, and practitioners in business and management area to reflect on current issues, challenges and opportunities, and to share the latest innovative research and best practice. This seminar brought together participants to exchange ideas on the future development of management disciplines: human resources, marketing, operations, finance, strategic management and entrepreneurship.
OCLC-licensed vendor bibliographic record.
Keywords: BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Entrepreneurship; Success in business -- Congresses; Management -- Congresses; Entrepreneurship -- Congresses